Effect of Cytozyme on Various Growth Rates of Sunflower in Relation to Resistance to Insect Pests - Murugesan, S; Gurusubramanian, G; Babu, A (Annals of Arid Zone, 2016)
The palisade characteristics of the leaves treated with a bacterial hydrolysate (cytozyme) with different dilutions on sunflower and its oil contents showed various degrees of resistance and susceptibility to insects. The palisad index of leaves treated with 1:8,000 appears to be more discriminative than the other palisad characteristics of leaves treated with 1:5,000.1:2,000 and control. Further, the palisad cells are more compactly arranged in the treated plants, compared with the control. The dimensional values of trichomes too increase proportionately with lowering concentration of the cytozyme which play a critical role in insect resistance.